Addressing the 2030 Bilingual Education Policy at Santo Yoseph Catholic Private High School: Issues and Resolutions - Kresna Ningsih Manik; Jamaluddin Nasution; Sahat Maringan Samosir; Merry Susanty Br Tarigan; Teguh Satria Amin; Nancy Angelia Purba (MASI Mandiri Edukasi, 2025)
Since the launch of the “Bilingual Policy for all schools supported by Yayasan Pendidikan Katolik (YPK) Don Bosco KAM in 2030,” schools have debated its impact. Teachers of non-English subjects worry about adapting, while parents fear their children may struggle with bilingual instruction. This quantitative study examines perceptions of students, teachers, parents, and staff at Santo Yoseph Catholic Private High School. The research explores key concerns: the necessity of the policy, its effect on local languages, feasibility by 2030, budget sufficiency, availability of qualified teachers, and whether non-English subject teachers can teach bilingually. A questionnaire with seven questions was distributed to 40 participants in Indonesian and later translated into English. Results show 60% believe bilingual education is essential, 10% disagree, 25% are uncertain, and 5% have no opinion. While over half support the policy, challenges remain, including limited funding, a shortage of trained bilingual teachers, and the need for more English classes and learning materials. Successful implementation requires the Don Bosco Catholic Education Foundation to increase funding and address these challenges to ensure smooth integration of bilingual education by 2030.